Handmade Bordir Sebagai Produk Unggulan Di Kota Probolinggo - Zaenullah; Mohammad Dullah Zulifatul Zuhriyah; Rachma Y (Community Development Journal, 2020)
AbstractEmbroidered craft in Indonesia is believed to be carried by many traders from China and India who carry out lots of buying and selling transactions in Indonesia, that's when these traders began to introduce embroidery crafts and their techniques. One of the leading industrial sectors is handmade products in the form of embroidery craft where initially in Probolinggo there was a center for embroidery industry but after the monetary crisis occurred in Indonesia since 1998 many craftsmen could not survive due to the high raw materials and the lack of buyers and the inability of craftsmen to reach other markets, leaving only a few that still exist today. This Community Service Activity Partner is Rizza Bordir. To achieve this goal, theCommunity Service activities are carried out using the Participatory Rural Appraisal Model (PRA), Community Development Model, through Persuasive and Educational Approaches. The results of this activity concluded that: Solving financial problems experienced by partners is to make software software, 2) Creation of new markets through online media in the form of Websites, Youtube, and Social Media is done by re-uploading files and images on IG, Facebook, Update Youtube Appearance and Start looking for Subsribe by promoting it through WA groups and Facebook, and Giving Hastage #RizzabordirProbolinggo so that the media will start to know Rizza Embroidery and can be read by Google.com and 3) That the help of tools in the form of Machines and E-commerce is expected to be maximized by Partners to be able to develop their business and increase turnover.Keywords: Rizza Embroidery, Handmade, E-Commerce